Outdoor development for managers - Bank, John (Gower, 1994)
The use of outdoor activity on management development programmes is growing steadily. John Bank's book, originally published in 1985, was the first full-length study of the subject and for this new edition he has revised the text throughout to take account of recent developments. It explains the underlying concepts, examines the relevance of outdoor training to management performance and reviews the range of philosophies and programmes available. Mr Bank draws extensively on the experience of people directly involved, both as trainers and as participants, and in ten fascinating case studies he shows how a variety of organizations use outdoor development in pursuit of their particular objectives.